A Systematic Review of Measurement Tools for the Proactive Assessment of Patient Safety in General Practice. Issue 5 (August 2021) - Lydon, Sinéad; Cupples, Margaret E.; Murphy, Andrew W.; Hart, Nigel; O'Connor, Paul
Abstract : Background: Primary care physicians have reported a difficulty in understanding how best to measure and improve patient safety in their practices. Objectives: The aims of the study were to identify measures of patient safety suitable for use in primary care and to provide guidance on proactively monitoring and measuring safety. Methods: Searches were conducted using Medline, Embase, CINAHL and PsycInfo in February 2016. Studies that used a measure assessing levels of or attitudes toward patient safety in primary care were considered for inclusion. Only studies describing tools focused on the proactive assessment of safety were reviewed. Two independent reviewers extracted data from articles and applied the Quality Assessment Tool for Studies with Diverse Designs. Results: More than 2800 studies were screened, of which 56 were included. Most studies had used healthcare staff survey or interviews to assess patient safety (n = 34), followed by patient chart audit (n = 14) or use of a practice assessment checklist (n = 7). Survey or interview of patients, active monitoring systems, and simulated patients were used with less frequency. Conclusions: A lack of appropriate measurement tools has been suggested to limit the ability to monitor patient safety in primary care and to improve patient care. There is no evident "best" method of measuring patient safety in primary care. However, many of the measures are readily available, quick to administer, do not require external involvement, and are inexpensive. This synthesis of the literature suggests that it is possible for primary care physicians to take a proactive approach to measuring and improving safety. Abstract : Supplemental digital content is available in the text.